2021
DOI: 10.1108/ijge-01-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Rural entrepreneurship and the context: navigating contextual barriers through women's groups

Abstract: PurposeThis study aims to examine how women's groups help women to navigate context-related barriers to their engagement in rural entrepreneurship. The paper combines the contextualisation of entrepreneurship framework and the feminist separatist theory to describe how women's groups in patriarchal rural communities enable women to circumvent context-related barriers and actively engage in rural entrepreneurship.Design/methodology/approachBased on a case study of 12 women's groups engaged in paddy farming, ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
2
0
3
Order By: Relevance
“…A segunda categoria intitulada "Práticas e características empreendedoras de mulheres rurais" foi a categoria que mais obteve artigos enquadrados, nove dos dezessete Outro artigo relevante colocado na mesma categoria "Desafios do empreendedorismo para mulheres do campo", denominado "Rural entrepreneurship and the context: navigating contextual barriersthrough women's groups", da Tanzânia, revelou que as mulheres rurais enfrentam desafios únicos relacionados ao contexto que as impedem de participar efetivamente do empreendedorismo rural (Semkunde et al, 2022).…”
Section: Silva Et Al 2008)unclassified
See 2 more Smart Citations
“…A segunda categoria intitulada "Práticas e características empreendedoras de mulheres rurais" foi a categoria que mais obteve artigos enquadrados, nove dos dezessete Outro artigo relevante colocado na mesma categoria "Desafios do empreendedorismo para mulheres do campo", denominado "Rural entrepreneurship and the context: navigating contextual barriersthrough women's groups", da Tanzânia, revelou que as mulheres rurais enfrentam desafios únicos relacionados ao contexto que as impedem de participar efetivamente do empreendedorismo rural (Semkunde et al, 2022).…”
Section: Silva Et Al 2008)unclassified
“…Os desafios apontados na pesquisa de Semkunde et al (2022) são o acesso limitado a terras agrícolas e mercados lucrativos, falta de redes de negócios, tempo limitado, pobreza e recursos financeiros insuficientes. Para superar tais desafios, as mulheres rurais se organizaram em grupos obter acesso a serviços de negócios, treinamento relacionado a negócios e formação de redes de negócios (SEMKUNDE et al, 2022).…”
Section: Silva Et Al 2008)unclassified
See 1 more Smart Citation
“…For example, the dominant picture emerging of women’s entrepreneurship in emerging economies in the literature is that of a marginalised group who engage in entrepreneurial activities out of necessity rather than opportunity (Brush and Cooper, 2012), and one which faces considerably more challenges compared to men in creating and running their enterprises (Afshan et al , 2021; Ammeer et al , 2021). However, recent scholarship and evidence drawing on the gender and diversity fields have shown that women entrepreneurs can and do successfully navigate such gendered assumptions in society (Stead, 2017) by using entrepreneurship as an empowering force to overcome environmental constraints and breaking free from the authority and dominance of others to pursue individual and collective development (Semkunde et al , 2022). Nevertheless, in emerging economies the potential emancipatory and empowering influence of women’s agency remains more muted.…”
Section: Introductionmentioning
confidence: 99%
“…Women's groups help women to overcome obstacles in developing rural entrepreneurship. Rural women organize themselves and their groups to gain access to business services and training, apply for grants, and develop business networks (Semkunde et al, 2022).…”
Section: Introductionmentioning
confidence: 99%